DAMPAK BANTUAN TERHADAP KESEJAHTERAAN PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN KECAMATAN SAMBAS - Muhammad Rio (Cross-border, 2018)
In order to increase the effectiveness of poverty alleviation and at the same time develop policies in the field of social protection, the Indonesian government in 2007 issued the Family Hope Program (PKH). The Family Hope Program (PKH) is a program that provides cash assistance to Very Poor Households (RTSM). In return, the RTSM is required to meet the requirements related to efforts to improve the quality of human resources (HR), namely education and health. The main objective of PKH is to reduce poverty and improve the quality of human resources, especially for the poor. This goal is also an effort to accelerate the achievement of the MDGs targets. Specifically, the objectives of PKH consist of: Improving the socio-economic conditions of RTSM, Improving the education level of RTSM children and Improving the health and nutritional status of pregnant women, postpartum mothers and children under 6 years of RTSM.